Política de recursos humanos na administração pública do Estado do Paraná: análise comparativa entre o discurso e a prática - Cimbalista, Silmara Nery (1998)
The aim of this dissertation is to demonstrate what happens to the public administration in the state of Paraná through a case study, more specifically, in two organization: one, called in specific legal regime, 'direct administration' and the other, 'indirect administration', by means of structured interviews searching the distance between the discourse and practice which concerns to what was developed in the training area inside a human resource policy of the state. Since two decades, the training function in public administration of the state is changing and suffering some internal (re)structures. These changes are due to the pressure generated by either the natural requirement of changing in the same area or in the ways and aims from governmental spheres (state and federal). On one hand, this study analyzes the performance of training function during from 1987 to 1994, in order to verify the outcome factors of the not structured area and the coherency between programmed and accomplished actions. On the other hand, compare the discourse and practice based on a human resource policy implemented and adopted by the government. The results of field research with bibliographic examination allow to conclude that although the official and formal documents delineate a human resource policy to the state, there were evident contradictions between the proposal and what the state really fulfilled. The qualitative data analysis concluded that the majority of the actions are implemented casuisticaly. During the case study period, the human resource area specifically, training and development, suffered constant (re) tructures. The consequence was ¿ the both institutions, responsible for the training area, lost time and financial resources. Legal changes, internal dispute for institutional space, lack of tune and synchrony resulted once more in a discontinued action in the area. However it is perceptible that the government is worried about the development and evaluation of its civil services although it goes on behaving without a structured and integrated planning related to any human resource system. The study, therefore, confirms that the formulation and implementation of effective human resource policy, either through an analytic model or not, must be centralized in integrated action interrelated to all the subsystems of the human resource area, neither in a disguised way nor linked to the discourse of a law or government projects.